Temperature expression patterns of genes and their coexpression with LncRNAs revealed by RNA-Seq in non-heading Chinese cabbage. (December 2016) - Song, Xiaoming; Liu, Gaofeng; Huang, Zhinan; Duan, Weike; Tan, Huawei; Li, Ying; Hou, Xilin
Abstract Background Non-heading Chinese cabbage (NHCC, Brassica rapa ssp.chinensis ) is an important leaf vegetable grown worldwide. However, little is known about the molecular mechanisms underlying tolerance for extreme temperature in NHCC. The limited availability of NHCC genomic information has greatly hindered functional analysis and molecular breeding. Results Here, we conduct comprehensive analyses of cold and heat treatments in NHCC using RNA-seq. Approximately 790 million paired-end reads representing 136, 189 unigenes with N50 length of 1705 bp were obtained. Totally, 14, 329 differentially expressed genes (DEGs) were detected. Among which, 10 DEGs were detected in all treatments, including 7 up-regulated and 3 down-regulated. The enrichment analyses showed 25 and 33 genes were enriched under cold and heat treatments, respectively. Additionally, 10, 001 LncRNAs were identified, and 9, 687 belonged to novel LncRNAs. The expression of miRNAs were more than that of pri-miRNAs and LncRNAs. Furthermore, we constructed a coexpression network for LncRNAs and miRNAs. It showed 67 and 192 genes were regulated by LncRNAs under cold and heat treatments, respectively. We constructed the flowchart for identifying LncRNAs of NHCC using transcriptome. Except conducting thede novo transcriptome analyses, we also compared these unigenes with the Chinese cabbage proteins. We identified several most important genes, and discussed their regulatory networks and crosstalk in cold and heat stresses. Conclusions We presented the first comprehensive characterization for NHCC crops and constructed the flowchart for identifying LncRNAs using transcriptome. Therefore, this study represents a fully characterized NHCC transcriptome, and provides a valuable resource for genetic and genomic studies under abiotic stress.